2017
DOI: 10.4172/2161-1165.1000300
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obesity Related Factors among Lebanese Adolescents: An Explanation for Gender and Socioeconomic Differences

Abstract: Background: The obesity-related factors in adolescents differ from one country to another. In Lebanon, those factors are still undetermined. Therefore, our purpose is to investigate the main determinants of overweight and obesity in Lebanese adolescents and to assess gender-specific differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In Lebanon, recent studies have suggested that a shift in adolescents' dietary intake, characterized by adherence to a westernized pattern of sedentary lifestyle, is associated with overweight and obesity and its comorbidities [25][26][27][28][29][30], which can persist throughout one's life and present health challenges [6][7][8][9][10][11]. With obesity rates far from global targets for 2025 (Global Nutrition report, 2025), adolescence provides an unequalled opportunity to establish healthy eating behaviors through health promoters, which could prevent obesity and related health problems later in life [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…In Lebanon, recent studies have suggested that a shift in adolescents' dietary intake, characterized by adherence to a westernized pattern of sedentary lifestyle, is associated with overweight and obesity and its comorbidities [25][26][27][28][29][30], which can persist throughout one's life and present health challenges [6][7][8][9][10][11]. With obesity rates far from global targets for 2025 (Global Nutrition report, 2025), adolescence provides an unequalled opportunity to establish healthy eating behaviors through health promoters, which could prevent obesity and related health problems later in life [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 39 mothers and 65.5 percent of mothers stopped breastfeeding by the time their child rached the age of six months and before one year, while 19.9% introduced solid foods by the age of four months. A study conducted among Lebanese adolescents comprising both low and middle socioeconomic groups showed these percentages to be higher, e.g., 41%, 70% and 41.6%, respectively [ 17 ]. The most common main reason for stopping breastfeeding in our sample was insufficiency of breastmilk (28.7%), closely followed by baby weaning himself/herself (24.8%).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that in developing countries, in contrast with developed ones, there is a general trend of increasing the prevalence of obesity with increasing SES [26]. In Lebanon, for example, people belonging to high socio-economic classes have more access to unhealthy food intake and are more sedentary though they practice more leisure activities [27]. In addition, children from high SES have access to personal television, tablets, or computers [27].…”
Section: Discussionmentioning
confidence: 99%
“…In Lebanon, for example, people belonging to high socio-economic classes have more access to unhealthy food intake and are more sedentary though they practice more leisure activities [27]. In addition, children from high SES have access to personal television, tablets, or computers [27]. This may explain the absence of a decrease in the odds of developing overweight or obesity among students of higher SES in private schools.…”
Section: Discussionmentioning
confidence: 99%